Program Heterogeneity and Propensity Score Matching: An Application to the Evaluation of Active Labor Market Policies - Lechner, Michael (The Review of Economics and Statistics, 2002)
This paper addresses microeconometric evaluation by matching methods when the programs under consideration are heterogeneous. Assuming that selection into the different subprograms and the potential outcomes are independent given observable characteristics, estimators based on different propensity scores are compared and applied to the analysis of active labor market policies in the Swiss region of Zurich. Furthermore, the issues of heterogeneous effects and aggregation are addressed. The results suggest that an approach that incorporates the possibility of having multiple programs can be an informative tool in applied work.